2001
DOI: 10.1002/bit.1128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of near‐infrared spectral information for rapid monitoring of bioprocess quality

Abstract: Access to real-time process information is desirable for consistent and efficient operation of bioprocesses. Near-infrared spectroscopy (NIRS) is known to have potential for providing real-time information on the quantitative levels of important bioprocess variables. However, given the fact that a typical NIR spectrum encompasses information regarding almost all the constituents of the sample matrix, there are few case studies that have investigated the spectral details for applications in bioprocess quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…For example, Vaidyanathan et al (2000) reported that using a polymertype supportive medium (PVP) to immobilize R. oryzae cells resulted in a LA yield of 71% and productivity 1.8 times higher than free filamentous mycelia. From a fermentation condition control perspective, there are many factors influencing the fungal pellet formation, such as nutrients, pH of medium, agitation, aeration, inoculum level, substrate concentration, polymer additives, viscosity of the medium, surface-active agents, etc.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vaidyanathan et al (2000) reported that using a polymertype supportive medium (PVP) to immobilize R. oryzae cells resulted in a LA yield of 71% and productivity 1.8 times higher than free filamentous mycelia. From a fermentation condition control perspective, there are many factors influencing the fungal pellet formation, such as nutrients, pH of medium, agitation, aeration, inoculum level, substrate concentration, polymer additives, viscosity of the medium, surface-active agents, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The region was manually chosen based on the chemistry of the system rather than allowing the computer to simply build a model with no analytical basis. The purpose of this article is to discuss the route from at-line to in-situ application of NIRS and simply present a successful model rather than discuss the different models and critically evaluate their performance relative to their complexity, since this topic has been addressed in the recent publications by Vaidyanathan et al (2000Vaidyanathan et al ( , 2001.…”
Section: At-line Model Developmentmentioning
confidence: 98%
“…It has been shown that multivariate data analysis (MVDA) using projection methods such as Principal Component Analysis (PCA), Partial Least Squares (PLS), and multiple regression can overcome challenges associated with biotech applications such as multidimensionality of the dataset, missing data and variation introduced by disturbing factors such as experimental error and noise (Johnson et al, 2007;Kourti, 2004;Martin and Morris, 2002). PCA has been applied to near-infrared spectral information derived from scanning unprocessed culture fluid samples from a complex antibiotic production process (Vaidyanathan et al, 2001). It was shown that changes in the spectral information that correspond to variations in the bioprocess can be identified and that the loadings and score plots can assist with process diagnosis and rapid assessment of process performance.…”
Section: Applications Using Chemometrics a Tool Mentioned In The Patmentioning
confidence: 99%